Recovery of the wave profile for irrotational periodic water waves from pressure measurements. (April 2015) - Kogelbauer, Florian
Abstract: Using a conformal hodograph transform and the governing equations for periodic traveling irrotational water waves, we obtain a relation between the bottom pressure and the free surface, expressed in terms of Fourier coefficients. This permits us to perform a formal asymptotic analysis that yields an approximate solution for the free surface provided the pressure at the flat bed is known.